(untitled) (The Batuk, 2020)
The study examines the predictability of index returns on the Dhaka stock market within the framework of the weak-form efficient market hypothesis using historical daily returns for a period of 1st June, 2014 to 29th May, 2020. The Jarque-Bera statistics test explored the return distribution of Dhaka Stock Exchange is non-normal. The random walk hypothesis (RWH) was tested using autocorrelation test, runs test, unit root tests(Augmented Dickey-Fuller (ADF) and, Phillip-Perron (PP) test) and variance ratio test. The results explored that all tests rejected the random walk hypothesis required by the weak-form efficient market hypothesis. This provides empirical basis to infer that the DSE is inefficient at weak-form and stock return can be predicted. The rejection of the RWH on a daily basis is possibly an indication that the weak-form inefficient characteristic of the DSE is not sensitive to return frequency.